2018
DOI: 10.1177/1467358417751025
|View full text |Cite
|
Sign up to set email alerts
|

Intention to visit India among potential travellers: Role of travel motivation, perceived travel risks, and travel constraints

Abstract: Several studies explain the direct effect of travel motivation, perceived risks, and travel constraints on visit intention. However, there are relatively limited investigations on the combined effect of these factors on visit intention. This study empirically tests a comprehensive model of visit intention based on travel motivation, perceived risks, and travel constraints. A quantitative study was performed on 316 university students in Malaysia. The results of the study found that travel motivation had a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 102 publications
(152 reference statements)
11
62
0
11
Order By: Relevance
“…Recent studies conducted in the US ( Frederiksen et al, 2020 ) also showed that a greater proportion of women than men self-report adherence to public health measures including avoiding social gatherings and travel, engaging in frequent hand hygiene, and stockpiling of food and medications. Furthermore, previous studies that have examined age ( Khan et al, 2018 ) have pointed out that younger tourists were less concerned about physical tourism-related risks and showed more travel intentions. Similarly, Neuburger and Egger (2020) demonstrated that older individuals were less likely to change their travel plans in the face of a risk threat, while Senbeto and Hon (2020) indicated that older tourists showed a decrease in taking trips even after the 2003 SARS outbreak and the 2015 avian flu outbreak in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Recent studies conducted in the US ( Frederiksen et al, 2020 ) also showed that a greater proportion of women than men self-report adherence to public health measures including avoiding social gatherings and travel, engaging in frequent hand hygiene, and stockpiling of food and medications. Furthermore, previous studies that have examined age ( Khan et al, 2018 ) have pointed out that younger tourists were less concerned about physical tourism-related risks and showed more travel intentions. Similarly, Neuburger and Egger (2020) demonstrated that older individuals were less likely to change their travel plans in the face of a risk threat, while Senbeto and Hon (2020) indicated that older tourists showed a decrease in taking trips even after the 2003 SARS outbreak and the 2015 avian flu outbreak in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Age. Khan, Chelliah, and Ahmed (2018) and Hajibaba et al (2015) found that age was a predictor of tourist risk perception and travel intentions. They discovered that younger tourists were less concerned about physical tourism-related risks and showed more travel intentions.…”
Section: Other Determinants Of Travel Intentionsmentioning
confidence: 99%
“…Travel constraints have attracted attention in the tourism literature, due to their effects on individuals' behavior [1,2]. A clearer understanding of travel constraints would help tourism and destination managers develop adequate promotional strategies for visitors [3]. Studies on travel constraints extended the original leisure constraints model (LCM) [4][5][6] established by [7] to explain perceived travel barriers [6,8,9].…”
Section: Introductionmentioning
confidence: 99%